DEKRIMINALISASI ABORSI BAGI KORBAN PERKOSAAN MENURUT PERATURAN PEMERINTAH NOMOR 61 TAHUN 2014 DITINJAU DARI PERSPEKTIF AGAMA, SOSIOLOGIS DAN PSIKOLOGIS - NPM. A2021161082, SUNARTI. R, S.Ag (Jurnal NESTOR Magister Hukum, 2018)
AbstractThis thesis entitled Decriminalization of abortion for rape victims according to Government Regulation No. 61 of 2014 viewed from the perspective of religion, sociology and psychological. The research aims to know, analyze, and explain about the impact of decriminalization of abortion for women who are victims of rape, as well as existing children in the womb, in terms of religious, sociological and psychological perspectives. Based on this the authors formulate 5 problems, namely: 1) How the view of Obstetric and Gynecologist and Midwife Specialist against the decriminalization of abortion for rape victims according to Government Regulation No. 61 of 2014, 2) How the views of the Religious Leaders against the decriminalization of abortion for rape victims according to Government Regulation Number 61 Year 2014, 3) How is the sociologist's view on the decriminalization of abortion for rape victims according to Government Regulation No. 61 of 2014, 4) How does the Psychologist view against the decriminalization of abortion for rape victims according to Government Regulation No. 61 of 2014, 5) How is the impact of the decriminalization of abortion, whether for women who are victims of criminal acts of rape, or children in their wombs, in terms of human rights and the interests of victims. The research method used is empirical normative legal research. The data required are primary and secondary data. Primary data was obtained by interviewing the respondents determined by non-probability sampling and purposive sampling, and by interviewing a resource person. While the secondary data obtained by reading and understanding in depth library materials related to the problem under study. Data analysis in this legal research is descriptive. Data that have been processed and obtained from the results of research, then analyzed by qualitative approach method, resulting in data that is descriptive analytical. Based on the results of the study, according to the Gynecologist and Midwife Doctor Viewpoint, Religious Leaders, Sociologists and Psychologists mostly answered in the interview guidelines strongly disagree on the decriminalization of rape victims. The author Concludes the decriminalization of abortion in Health Act and Government Regulation No. 61 of 2014 is acceptable for health reasons of rape victims according to the view of Obstetric and Gynecology Specialist dr. Yustinus Charles A, SpOG, The overall conclusion of interviews with religious leaders that the decriminalization of abortion in the Health Act and Government Regulation No. 61 of 2014 is acceptable on humanitarian grounds, The overall conclusion of interviews with sociologist Dr. Kristianus Atok, M.Si that the decriminalization of abortion in the Health Act and Government Regulation No. 61 of 2014 is acceptable for humanitarian reasons and strongly affects the social relations of rape victims, and the overall conclusion of interviews with psychological figures Dr Drs. Andreas Muhrotien, M.Si that the decriminalization of abortion in Health Act and Government Regulation No. 61 of 2014 can be accepted with humanitarian reasons and greatly affect the psychological development of rape victims.Keywords: Decriminalization, Abortion, Rape